Do corporate taxes hinder innovation? - Mukherjee, Abhiroop; Singh, Manpreet; Žaldokas, Alminas (Journal of Financial Economics, 2017)
We exploit staggered changes in state-level corporate tax rates to show that an increase in taxes reduces future innovation. A variety of tests, including those based on policy discontinuity at contiguous counties straddling borders of politically similar states, show that local economic conditions do not drive our results. The effect we document is consistent across the innovation spectrum: taxes affect not only patenting and R&D investment but also new product introductions, which we measure using textual analysis. Our empirical results are consistent with models that highlight the role of higher corporate taxes in reducing innovator incentives and discouraging risk-taking.